2020
DOI: 10.1021/acs.jpclett.0c02564
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field-Mediated Control of Whole-Cell Biocatalysis

Abstract: For decades, scientists have been looking for a way to control catalytic and biocatalytic processes through external physical stimuli. In this Letter, for the first time, we demonstrate the 150 ± 8% increase of the conversion of glucose to ethanol by Saccharomyces cerevisiae due to the application of a low-frequency magnetic field (100 Hz). This effect was achieved by the specially developed magnetic urchin-like particles, consisting of micrometer-sized core coated nanoneedles with high density, which could pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
7
3
Order By: Relevance
“…Based on the results of cell counting and membrane permeability experiments, it could be concluded that US-induced sublethal membrane damage was waned with the presence of non-proteolysis PC on the surface of nanoparticles, and the non-proteolysis PC might result in smaller membrane pores than full-proteolysis PC. Previous research showed that the small hole (a pore size < 50 nm) on the membrane could be repaired immediately in 5 to 120 s [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of cell counting and membrane permeability experiments, it could be concluded that US-induced sublethal membrane damage was waned with the presence of non-proteolysis PC on the surface of nanoparticles, and the non-proteolysis PC might result in smaller membrane pores than full-proteolysis PC. Previous research showed that the small hole (a pore size < 50 nm) on the membrane could be repaired immediately in 5 to 120 s [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…This format of biotransformation has been used in different biotransformation processes due to several advantages, such as high surface-area-to-volume ratio, high catalytic activity, and low energy requirements ( Pinto et al, 2020 ; Liu et al, 2019 ). However, the whole-cell biocatalysis approach presents some disadvantages related to the low diffusion rate of the substrate into the cell to the reaction centers, where takes place the enzymatic reaction ( Kladko et al, 2020 ), which leads to low stability, cross reactivity, impossibility to recycle the biocatalyst and time-consuming purification steps ( Sheldon and Woodley, 2018 ; Haghighatian et al, 2020 ).
Fig.
…”
Section: Biocatalytic Systems To Remove Psychiatric Drugs From Wastew...mentioning
confidence: 99%
“…In contrast to treatment, the use of nanoparticles in microbial engineering is less widespread in the literature. Examples include protective nanoshells to overcome conditions in harsh environments [ 144 , 145 ], the integration of synthetic solar-to-chemical energy transformation pathways in non-photosynthetic organisms [ 146 , 147 ], and magnetic and light control of metabolic reactions [ 14 , 148 ]. The synergy of synthetic biology and materials science creates a unique possibility for the novel generation of microbes-based factories with remote control and the on-demand production of valuable products.…”
Section: Biological Effect and Applicationmentioning
confidence: 99%
“…The shape control of nanomaterials represents a major field in materials science, and a large number of approaches exist towards the production of sphere- [8], ellipsoid- [9], dumbbell- [10], cube- [11], polyhedra- [12], rod- [13], urchin- [14], star- [15], chain- [16], ribbon- [17], hollow [18], prism- [19], and hexagon-shaped [20] nanomaterials. Nanomaterial shape control stems from effects such as selective adsorption growth of reactive facets; spontaneous aggregation and agglomeration; seeded growth on particularly-shaped templates; controllable crystal fusion via orientation attachment; self-assembly via selective strong interactions, e.g., chemical and hydrogen bonds; and Ostwald ripening directed at free surface energy minimization.…”
Section: Introductionmentioning
confidence: 99%